PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM DAN DANA PERIMBANGAN TERHADAP PELAKSANAAN OTONOMI DAERAH KABUPATEN MAMUJU - Fajariani, Nur (GROWTH Jurnal Ilmiah Ekonomi Pembangunan, 2019)
In this study, several things were explained, including; 1). regional financial ratios for the past 5 (five) years 2). The Effect of Regional Revenue, General Allocation Funds and Balancing Funds on the implementation of regional autonomy in Mamuju Regency, West Sulawesi. This study uses qualitative analysis and quantitative analysis which uses variables using the formula of regional financial ratios, multiple linear regression analysis and performs the t test and F test to answer hypotheses. The results showed that: 1). Judging from the financial ratios in the Mamuju Regency it is still lacking so the Mamuju Regency government still relies on the central government, 2). In the regression analysis of the three independent variables (X1, X2 and X3) simultaneously there was no significant effect on the dependent variable (Y), because the three dependent variables showed the value of Tcount ≤ Ttable or sig ≥ 0.05, meaning Ho was accepted and H1, H2 and H3 is rejected. While based on the correlation analysis shows that the Regional Original Revenue, the General Allocation Fund and the Balancing Fund have a strong and positive influence (+) on the Regional Autonomy Implementation in Mamuju Regency, West Sulawesi, where an R value of 0.669 is indicated and the coefficient of determination or R square is 0.447.